(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Yunus Rajabi, one of the leading representatives of Uzbek music, is a skilled musician, an accomplished hafiz with a unique style of performance, a collector of the priceless spiritual wealth of the Uzbek people, and a great teacher who established a school of example for everyone as a passionate leader. At the same time, the activity of the owner of high potential in the compositional creativity is also noteworthy. This article discusses the creation history and musicaltheoretical analysis of one of the artist’s best works, “Ne navo soz aylagay” (“Judo”), which is loved and listened to by music connoisseurs.